Optical characteristics and application of carbon-nanotube-based saturable absorber with a spiral scheme. (25th November 2019) - Yang, Huiran; Wang, Guomei; Li, Wenlei; Sun, Yuhang
Abstract: A carbon-nanotube-based saturable absorber (CNT-SA) with a spiral scheme is proposed, which is obtained by twining CNT-polymer filaments around a microfiber. The proposed CNT-SA possesses many advantages, such as high thermal damage threshold, excellent oxidation resistance, and long-distance evanescent field interaction. Nonlinear absorption of this CNT-SA is measured, giving saturable absorption and saturable intensity of ∼5.02% and ∼172.2 MW cm −2, respectively. Based on the CNT-SA, an Er-doped fiber laser is achieved. The experimental results open up venues to create a new type of SA for ultrafast lasers.